A Predictive Model for Acute Respiratory Distress Syndrome Mortality Using Red Cell Distribution Width - Ala Alkhatib; Lori Lyn Price; Rania Esteitie; Peter LaCamera (Critical Care Research and Practice)
Methods. This observational retrospective cohort study includes 318 ARDS patients extracted from an ICU database between the years of 2001 and 2008. Clinical factors including age, gender, comorbidity score, Sequential Organ Failure Assessment (SOFA) score, and PaO2/FiO2 ratio were chosen for the base model to predict ICU mortality. The RDW value at the time of ARDS diagnosis was added to the base model to determine if it improved its predictive ability. Results. 318 subjects were included; 113 (36%) died in the ICU. AUC for the base model without RDW was 0.76, and 0.78 following the addition of RDW [p=0.048]. The NRI was 0.46 (p=0.001), indicating that, in 46% of patients, the predictive probability of the model was improved by the inclusion of RDW. Conclusions. Adding RDW at time of ARDS diagnosis improved discrimination in a model using 4 clinical factors to predict ICU mortality.